2016
DOI: 10.1038/oncsis.2016.19
|View full text |Cite
|
Sign up to set email alerts
|

A porcine model of osteosarcoma

Abstract: We previously produced pigs with a latent oncogenic TP53 mutation. Humans with TP53 germline mutations are predisposed to a wide spectrum of early-onset cancers, predominantly breast, brain, adrenal gland cancer, soft tissue sarcomas and osteosarcomas. Loss of p53 function has been observed in >50% of human cancers. Here we demonstrate that porcine mesenchymal stem cells (MSCs) convert to a transformed phenotype after activation of latent oncogenic TP53R167H and KRASG12D, and overexpression of MYC promotes tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 56 publications
1
54
0
Order By: Relevance
“…However, it is conceivable that the “three drivers” model we propose in this review more closely mimics the development of aggressive OS since the majority of the GEMMs generated so far have a much longer latency. Furthermore, a recent study demonstrated that three sequential mutations in p53, Kras, and Myc can convert wild-type porcine mesenchymal stem cells (MSCs) into sarcoma cancer cells, mimicking key molecular aspects of human sarcomagenesis [12]. Our proposed model correlating the number of drivers and tumor latency is also in line with a mathematic model generated by epidemiology studies of a large colon cancer cohort, which found that only three driver gene mutations are required for the development of lung and colorectal cancers [76].…”
Section: Understanding the Role Of Driver Gene Mutations In The Dementioning
confidence: 99%
See 2 more Smart Citations
“…However, it is conceivable that the “three drivers” model we propose in this review more closely mimics the development of aggressive OS since the majority of the GEMMs generated so far have a much longer latency. Furthermore, a recent study demonstrated that three sequential mutations in p53, Kras, and Myc can convert wild-type porcine mesenchymal stem cells (MSCs) into sarcoma cancer cells, mimicking key molecular aspects of human sarcomagenesis [12]. Our proposed model correlating the number of drivers and tumor latency is also in line with a mathematic model generated by epidemiology studies of a large colon cancer cohort, which found that only three driver gene mutations are required for the development of lung and colorectal cancers [76].…”
Section: Understanding the Role Of Driver Gene Mutations In The Dementioning
confidence: 99%
“…Overall, our understanding of the molecular basis of OS development has dramatically improved by using a cross-species approach, especially through GEMMs. Other publications on modeling OS using mouse, rat, dog, pig, and zebrafish exist, but will not be described in detail in this review [12, 26, 27, 85-88]. …”
Section: Understanding the Role Of Driver Gene Mutations In The Dementioning
confidence: 99%
See 1 more Smart Citation
“…These transformed porcine MSCs, with genomic instability and complex karyotypes, had the ability to develop into sarcomas upon transplantation into immunodeicient mice [15]. Other models also indicated that intrabone or periosteal inoculation of p53−/− or p53−/−RB−/− BM-MSCs or ASCs originated metastatic osteoblastic osteosarcoma (OS).…”
Section: G12dmentioning
confidence: 99%
“…The latter group has been used in lymphoma and osteogenic tumor development under the induction of tumorigenesis in primary hematopoietic and broblastic cells, respectively. [9,13,14] Furthermore, swine primary cell lines have been established from different anatomic tissues such as mammary glands [11], kidney [12], intestine [15], trachea [12], lung [16], and alveoli [20]. These primary cells were used to evaluate gene expression patterns, drug susceptibility and cell physiology [22].…”
Section: Introductionmentioning
confidence: 99%